Criminology in Islam; between Human-Kind and Injustice - Hasan, Hamzah (Mazahibuna: Jurnal Perbandingan Mazhab, 2021)
This article aims to highlight controversies regarding the punishment for criminals. Some legal experts consider that punishment in Islamic crimes is contrary to human rights standards. Such differences are reasonable due to differences in standards in viewing human rights. According to Islamic criminal law, human rights are centred on God (theocentric), while according to criminal law, human rights are human-centred (anthropocentric). On that basis, Islamic criminal law views punishing people who commit crimes with any form of punishment does not conflict with human rights because the perpetrators have sacrificed other people. just Islamic criminal law upholds humanity and justice